Narrative Review: Cardiotoxicities and Cardiac-Sparing Techniques in Radiotherapy - Maria F. Chan PhD; Dhwani Parikh MD; Chengyu Shi PhD (Technology in Cancer Research & Treatment)
This review article aims to synthesize existing data on radiation-induced heart diseases in patients undergoing chest radiation therapy and also explores cardiac-sparing techniques to mitigate cardiotoxic effects. We conducted a comprehensive database search to review and consolidate data regarding chest radiotherapy and effects on the heart as well as techniques to minimize exposure to the heart. The research findings demonstrate associations between radiation exposure to cardiac substructures and subsequent cardiotoxicity. This review also stresses the importance of identifying patients at high-risk for cardiotoxicity as well as advocates for the adoption of stringent cardiac dose constraints in these patients. Advanced cardiac-sparing techniques, notably respiratory motion management, have emerged as pivotal strategies to minimize the likelihood of cardiac events. This narrative review emphasizes the critical role of these innovations in optimizing cardiac health during radiation treatment.